Pencegahan Penularan Covid-19 dengan 3M di Kelurahan Rappokalling Makassar - Nur Wahyuni Munir; Rizqy Iftitah Alam (PT.Mantaya Idea Batara, 2021)
Covid-19 can affect everyone including infants, children, adults, and the elderly. However, people with the highest risk factors are the elderly. The purpose of this service activity is to provide health education about Covid-19 and ways to prevent its spread to the elderly and their families. The methods used are lectures, discussions, and demonstrations. Counseling material about the definition of covid-19, the causes and methods of transmission of the corona virus, symptoms of covid-19, and how to prevent covid-19 with 3M. The counseling begins with a pretest and ends with a posttest. After being given counseling, the level of knowledge of residents about preventing the transmission of Covid-19 with 3M increased from where previously there were only 5 people (33%) who had good knowledge, after being given counseling increased to 12 people (80%).